High-level production of L-valine in Escherichia coli using multi-modular engineering. (September 2022) - Hao, Yanan; Pan, Xuewei; Xing, Rufan; You, Jiajia; Hu, Mengkai; Liu, Zhifei; Li, Xiangfei; Xu, Meijuan; Rao, Zhiming
Graphical abstract: Highlights: ARTP mutagenesis was applied for constructing L-valine-producing strain. Transcription factors associated with L-valine biosynthesis were investigated. Modification of PdhR and RpoS increased the production of L-valine. Entner-Doudoroff pathway from Zymomonas mobilis promoted NADPH regeneration. The titer of L-valine reached 92 g/L in 5 L bioreactor. Abstract: L-valine is a valuable amino acid in mammals that is used as the main component of feed additives. The low efficiency of the fermentation titer limits the industrial application of L-valine. Here, an L-valine-producing strain of Escherichia coli was obtained using a multi-modular strategy. Initially, a chassis strain was generated by mutagenesis and high-throughput screening. The L-valine biosynthetic pathway and transport module were modified to improve the L-valine titer. Subsequently, the transcription factors associated with L-valine biosynthesis were investigated. Overexpression of PdhR and inhibition of the expression of RpoS promoted L-valine synthesis. Finally, the NADPH supply was enhanced after the introduction of the heterologous Entner-Doudoroff (ED) pathway from Zymomonas mobilis . The strain VAL38 produced 92 g/L L-valine in a 5-L bioreactor with a yield of 0.34 g/g glucose. This strategy is provided as a reference for improving the production performance of cell factories for L-valine and its derivatives.